2022
DOI: 10.1186/s13019-022-01874-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender differences on hemostasis in patients after coronary artery bypass grafts surgeries in the context of tranexamic acid administration

Abstract: Background Sex differences present in the blood management of patients after coronary artery bypass grafts (CABG) surgeries. Tranexamic acid (TXA) performed well in maintaining hemostasis during and after surgeries. However, the impact of sex differences on blood control after CABG in patients who received TXA was not investigated. Methods Overall, 29,536 patients undergoing CABG with TXA administration from 2009 to 2019 in our hospital were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Similarly, in urgent surgeries, females had an almost 2 times higher probability of requiring transfusion compared to males (60.38% vs 33.29%, respectively). These results are supported by previous studies, which demonstrated that regardless of tranexamic acid use, females had less blood loss after CABG, although the risk for postoperative transfusion was higher [ 22 ].…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, in urgent surgeries, females had an almost 2 times higher probability of requiring transfusion compared to males (60.38% vs 33.29%, respectively). These results are supported by previous studies, which demonstrated that regardless of tranexamic acid use, females had less blood loss after CABG, although the risk for postoperative transfusion was higher [ 22 ].…”
Section: Discussionsupporting
confidence: 86%